2014
DOI: 10.1016/j.dld.2014.08.034
|View full text |Cite|
|
Sign up to set email alerts
|

Tobacco smoking and intestinal metaplasia: Systematic review and meta-analysis

Abstract: The weak and non-statistically significant association found through meta-analysis of the available evidence does not confirm smoking as an independent risk factor for intestinal metaplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 63 publications
(121 reference statements)
2
14
0
Order By: Relevance
“…Taken together, these may have contributed to conservative PAF estimates, though not compromising the comparison across regions. To further improve the accuracy of our estimates of PAF, we used sex-specific summary RRs, to account for differences in the patterns of smoking between men and women, and we assumed a time lag of approximately 10 years between exposure to smoking and occurrence of cancer, which is supported by the available evidence on the relation between smoking and gastric cancer precursor lesions [16]. This may have contributed to more accurate estimates of the burden of gastric cancer attributable to smoking than in previous studies, which took into account a smaller [21] or no lag time [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these may have contributed to conservative PAF estimates, though not compromising the comparison across regions. To further improve the accuracy of our estimates of PAF, we used sex-specific summary RRs, to account for differences in the patterns of smoking between men and women, and we assumed a time lag of approximately 10 years between exposure to smoking and occurrence of cancer, which is supported by the available evidence on the relation between smoking and gastric cancer precursor lesions [16]. This may have contributed to more accurate estimates of the burden of gastric cancer attributable to smoking than in previous studies, which took into account a smaller [21] or no lag time [26].…”
Section: Discussionmentioning
confidence: 99%
“…For this, we used country-specific data on smoking prevalence and gastric cancer incidence and published estimates of the magnitude of the association between smoking and gastric cancer. A time lag of approximately 10 years was assumed, based on the stronger associations observed between smoking and cancer or intestinal metaplasia [15,16] than with the preceding gastric lesions, indicative of an effect later in carcinogenesis.…”
Section: Methodsmentioning
confidence: 99%
“…Gastric and intestinal metaplasia upon nicotine administration was recently reported by Morais et al . (). The significant increase in gastrin concentrations in nicotine‐treated animals might explain the gastric erosions that have been seen upon macroscopic examination of the stomach of nicotine‐treated rats, because gastrin is an important stimulator to gastric acid secretion.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have also examined the relationship between smoking and the gastric IM (10)(11)(12). A recent meta-analysis with 19 articles reported a weak and statistically nonsignificant association of smoking with IM using available data but could not confirm smoking as an independent risk factor for IM (12).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the association between smoking and IM has been examined in observational studies, but the results are controversial (10,11). A recent study involving a meta-analysis reported a statistically nonsignificant association between smoking and IM, suggesting that further research is needed (12). Indeed, many studies were limited by their cross-sectional design, unclear temporality between exposure and outcome, insufficient sample size, and the use of self-report smoking status.…”
Section: Introductionmentioning
confidence: 99%